Optimalisasi Pemetaan Potensi Desa Berbasis Teknologi Geospasial untuk Perencanaan Desa Tebul Timur: Enhancing Village Potential Mapping with Geospatial Technology to Support Tebul Timur Planning - Rahmawati, Fithriyah; Risdiana, Faraniena Yunaeni; Wardi, Moch. Cholid; Listiana, Heni (PengabdianMu: Jurnal Ilmiah Pengabdian kepada Masyarakat, 2026)
The community service activity initiated by the community service team aims to apply geospatial technology to identify and visualize the potential of Tebul Timur Village, Pamekasan. Asset-Based Community Development (ABCD) was an approach applied that involved the active participation of the community in collecting and validating data. The method included field surveys, data collection of coordinates, participatory discussions, and data processing using geospatial technology. The results show that geospatial technology can systematically integrate spatial and non-spatial data to represent the area’s potential. The mapping results reveal that Tebul Timur Village has diverse potential in human resources, agriculture, and water availability. One standout potential is the durian fruit, unique to the Pegantenan District, mostly grown in residents’ yards. Thus, geospatial technology can be used to support data-driven asset mapping.